PEMAKNAAN HADIS ANJURAN MENUNTUT ILMU RIWAYAT MUSLIM DARI ABU HURAIRAH DI KALANGAN AKADEMISI KOTA AMBON - Rustina Nurdin (IAIN Manado, 2021)
Abstract: This study aims to analyze the meaning of Ambon City academics on the Prophet's hadith regarding the recommendation to study from Abu Hurairah ra. Muslim history. This type of research is descriptive qualitative research. The research object of the Prophet's hadith. about suggestions and orders to actively seek knowledge for his people. The research subjects are academics; lecturers, teachers and students who live in the city of Ambon. Determination of informants is done through purposive sampling technique, data collection is done through observation, in-depth interviews and documentation. The data analysis was carried out through two analytical techniques; 1) the analysis of the meaning of the hadith was carried out through the tahliliy method; 2) through qualitative data analysis techniques, namely data display, data verification, data interpretation and drawing conclusions. The results of the study are stated as follows that the meaning of this hadith among academics in Ambon City is in line and in accordance with what has been explained by hadith scholars. Most academics interpret this hadith in a meaningful or contextual way that the science referred to in this hadith is the science of religion and general science (not only religious science), seeking knowledge is like worship which is a basic human spiritual need, and heaven (al-jannah) is meant. is success and happiness that will be obtained in this world and in the hereafter for those who are serious about learning and seeking knowledge. Key Words: hadith; recommendation to study; academics Abstrak: Penelitian ini bertujuan untuk menganalisis pemaknaan akademisi Kota Ambon terhadap hadis Nabi saw tetang anjuran menuntut ilmu dari Abu Hurairah ra. riwayat Muslim. Jenis penelitian ini adalah penelitian deskriptif kualitatif. Obyek penelitian hadis Nabi saw. tentang anjuran dan perintah giat mencari ilmu bagi ummatnya. Adapun subyek penelitian adalah akedemisi; dosen, guru dan mahasiswa yang berdomisili di kota Ambon. Penentuan informan dilakukan melalui teknik purposive sampling, pengumpulan data dilakukan melalui observasi, wawancara mendalam dan dokumentasi. Adapun analisis data dilakukan melalui dua teknik analisis;1) analisis makna hadis ditempuh melalui metode tahliliy; 2)melalui teknik analisis data kualitatif, yaitu display data, verifikasi data, interpretasi data dan penarikan kesimpulan. Hasil penelitian dikemukakan sebagai berikut bahwa pemaknaan hadis ini di kalangan akademisi Kota Ambon sejalan dan sesuai dengan apa yang telah dijelaskan oleh ulama hadis. Sebagian besar akademisi memaknai hadis ini secara maknawiyah atau kontekstual bahwa ilmu yang dimaksud dalam hadis ini adalah ilmu agama dan ilmu umum (bukan hanya ilmu agama), menuntut ilmu ibarat ibadah yang merupakan kebutuhan pokok rohani manusia, serta surga (al-jannah) yang dimaksud adalah kesuksesan dan kebahagiaan yang akan diperoleh di dunia ini maupun di akhirat kelak bagi mereka yang bersungguh-sungguh belajar dan menutut ilmu. Kata Kunci: hadis; anjuran menuntut ilmu; akademisi